Comparing Hydrolysis and Transglycosylation Reactions Catalyzed by Thermus thermophilus β-Glycosidase. A Combined MD and QM/MM Study - Romero-Téllez, Sonia; Lluch, José M.; González-Lafont, Àngels; Masgrau, Laura (Frontiers in Chemistry, 2019)
The synthesis of oligosaccharides and other carbohydrate derivatives is of relevance for the advancement of glycosciences both at the fundamental and applied level. For many years, glycosyl hydrolases (GHs) have been explored to catalyze the synthesis of glycosidic bonds. In particular, retaining GHs can catalyze a transglycosylation (T) reaction that competes with hydrolysis (H). This has been done either employing controlled conditions in wild type GHs or by engineering new mutants. The goal, which is to increase the T/H ratio, has been achieved with moderate success in several cases despite the fact that the molecular basis for T/H modulation are unclear. Here we have used QM(DFT)/MM calculations to compare the glycosylation, hydrolysis and transglycosylation steps catalyzed by wild type Thermus thermophilus β-glycosidase (family GH1), a retaining glycosyl hydrolase for which a transglycosylation yield of 36 % has been determined experimentally. The three transition states have a strong oxocarbenium character and ring conformations between 4H3 and 4E. The atomic charges at the transition states for hydrolysis and transglycosylation are very similar, except for the more negative charge of the oxygen atom of water when compared to that of the acceptor Glc. The glycosylation transition state has a stronger SN2 character than the deglycosylation ones and the proton transfer less advanced. At the QM(PBE0/TZVP)/MM level, the TS for transglycosylation has shorter O4GLC-C1FUC (forming bond) distance and longer OE2GLU338-C1FUC (breaking) distance than the hydrolysis one, although the HACC proton is closer to the Glu338 base in the hydrolysis TS. The QM(SCC-DFTB)/MM free energy maxima show the inverted situation, although the hydrolysis TS presents significant structural fluctuations. The 3-OHGLC group of the acceptor Glc (transglycosylation) and WAT432 (neighbor water in hydrolysis) are identified to stabilize the oxocarbenium transition states through interaction with O5FUC and O4FUC. The analysis of interaction suggests that perturbing the Glu392-Fuc interaction could increase the T/H ratio, either by direct mutation of this residue or indirectly as reported experimentally in the Asn390I and Phe401S cases. The molecular understanding of similarities and differences between hydrolysis and transglycosylation steps may be of help in the design of new biocatalysts for glycan synthesis.